DISSEMINATION METHOD FOR STANDARD METER RATIO USING TWO DC VOLTAGE STANDARD SOURCES - Hadi Sardjono (Badan Standardisasi Nasional, 2018)
ABSTRACT Since 2004, Research Center for Metrology – Indonesian Institute of Sciences (RCM – LIPI) has maintained the DC voltage standard traceability from 1.018 V up to 1000 V based on two standard source types, that work as secondary standards, namely standard cell groups and a multifunction calibrator. In this research, a new method was developed in maintaining the tertiary standard accuracy using a ratio meter. The accuracy of the standard meter ratio could be achieved by a dissemination process. This dissemination process was validated using an error number (En) through a comparison between two voltage standards obtained from indirect measurement method and direct measurement method. The result showed that the standard meter ratio validated on 3 ranges of comparison measurement namely 1.018:1.018, 1.018:10, and 1.018:100 gave En values of 0.87, 0.05, and -0.041 respectively.